Simulation and analysis of surge protector circuit - Lim, Chang Hong (Nanyang Technological University, 2021)
Transient surges events are problematic in electrical distribution system because they adversely affect electronic equipment. The impact of the disruption can range from reduced lifespan of equipment to complete failure of equipment function. Transients are caused by both natural phenomena and electrical equipment. The best example of the former is a lightning strike, which can produce currents as high as thousands of amperes. Some examples of the latter are motors, transformers, and switching power supplies. A surge protection device or a surge protector is used to protect electronic equipment from transients by limiting or clamping the supplied voltage to a safe level. In this project, surge protection component will be identified based on factors such as clamping voltage, joule rating, and response time. After which, the surge protection circuit will be designed and simulated in LTspice to prove that the design works. In addition, a filtering circuit would be added to explore the effect of the filtering circuit during a transient event. A physical prototype circuit board would be designed in Eagle software and manufactured. The filtering circuit would then be added to the physical prototype to undergo testing under transient condition. Component from the circuit designed in the simulation would be soldered onto the board and tested to test the simulation results. Finally, the best performing filter will then be compared to similar commercial product to compare the cost efficiency of the project.